2015
DOI: 10.1007/s10526-015-9665-4
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific competition between Anagyrus pseudococci and Leptomastix dactylopii, parasitoids of the vine mealybug Planococcus ficus

Abstract: Interspecific competition among parasitoids plays a key role in the population dynamics of insect pests and may affect the outcome of biological control programs. The aim of this study was to examine competition between two parasitoids, Anagyrus pseudococci (Girault) and Leptomastix dactylopii Howard (Hymenoptera: Encyrtidae), of the vine mealybug Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae) under laboratory conditions. The mealybug was parasitized by both parasitoid species at the same time (withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…may be more affected than L. dactylopii; in fact, when the latter had parasitism priority for 72 h, its emergence rate was approximately 95%, while parasitism priority by A. pseudococci s.l. led to an emergence rate of 77.5% (Muştu and Kilinçer 2015). Although inoculative releases of L. dactylopii in vineyards could affect the activity of A. pseudococci s.l., Muştu and Kilinçer (2015) believe that parasitoid combination might be more successful than single use of natural enemies.…”
Section: Intraguild Interactions Among Natural Enemies Of Planococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…may be more affected than L. dactylopii; in fact, when the latter had parasitism priority for 72 h, its emergence rate was approximately 95%, while parasitism priority by A. pseudococci s.l. led to an emergence rate of 77.5% (Muştu and Kilinçer 2015). Although inoculative releases of L. dactylopii in vineyards could affect the activity of A. pseudococci s.l., Muştu and Kilinçer (2015) believe that parasitoid combination might be more successful than single use of natural enemies.…”
Section: Intraguild Interactions Among Natural Enemies Of Planococcusmentioning
confidence: 99%
“…led to an emergence rate of 77.5% (Muştu and Kilinçer 2015). Although inoculative releases of L. dactylopii in vineyards could affect the activity of A. pseudococci s.l., Muştu and Kilinçer (2015) believe that parasitoid combination might be more successful than single use of natural enemies.…”
Section: Intraguild Interactions Among Natural Enemies Of Planococcusmentioning
confidence: 99%
“…Türkiye'de meyve ağaçlarındaki unlubit türlerinin doğal düşmanları Table 1. Natural enemies of mealybug species injurious in fruit trees in Türkiye Planococcus citri'nin doğal düşman türleri (Lodos 1982;Öncüer 1991;Kaydan et al 2006;Anonymous 2007;Demirci et al 2008;Japoshvili & Çelik 2010;Kılınçer et al 2010;Yayla 2010;Kurt & Karaca 2016;Birişik et al 2017 (Ülgentürk et al, 2002;Güleç et al, 2007;Demirci et al, 2008;Japoshvili & Çelik, 2010;Kaydan & Japoshvili, 2010;Muştu & Kılınçer, 2015;Anonymous, 2018;Japoshvili et al, 2018) (Ülgentürk et al, 2002;Kaydan, 2004;Ülgentürk et al, 2004;Kaydan et al, 2006;Japoshvili & Çelik, 2010;Yayla, 2010) Ülkemizde P.viburni ve N. nipae'nin doğal düşmanları ile ilgili herhangi bir çalışmaya rastlanılmamış olmakla birlikte, bu unlubit türlerinin doğal düşmanları olarak Nephus spp., C. montrouzieri, Scymnus spp., L. dactylopii ve Anagyrus spp. meyve bahçelerimizde bulunmaktadır (Anonymous, 2017d, h, k).…”
Section: üRünde Verim Ve Kalite Kaybıunclassified
“…Leptomastix dactylopii is a solitary koinobiont endoparasitoid. It prefers the 3rd nymph and young female stages of the host (Muştu and Kılınçer 2015). Although the homeland of L. dactylopii was previously thought to be Brazil (Compere 1939), recent studies reported that it might be originated from Africa (Kol-Maimon et al 2015).…”
Section: Introductionmentioning
confidence: 99%